The Continuous Classical Optimal Control for a Coupled Nonlinear Parabolic Partial Differential Equations with Equality and Inequality Constraints - Al-Hawasy, Jamil A Ali; Kadhem, Ghufran M (Al-Nahrain Journal of Science, 2018)
his paper is concerned with the existence and uniqueness state vector solution for a coupled of nonlinear parabolic equations using the Galerkin method when the continuous classical control vector is given, the existence theorem of a continuous classical optimal control vector with equality and inequality vector state constraints is proved, the existence and uniqueness solution of the adjoint equations associated with the state equations is studied. The derivation of the Frcéhet derivative of the Hamiltonian is obtained. Finally the necessary conditions theorem, so as the sufficient conditions theorem of optimality of the constrained problem are proved.